(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2023)
In this paper an aesthetics is proposed based on the De Martino concept of “crisis of presence”. If one takes such a terrifying notion seriously a very different idea of art can be experienced, an art suited in the apocalyptic time of the “end of the world”. An art that can only begin when the fear for the non-human and materic in us is set aside.